Acquired cryptorchidism: More harm than thought?. Issue 4 (August 2016) - Promm, M.; Schröder, A.; Neissner, C.; Eder, F.; Rösch, W.H.; Schröder, J.
Summary: Introduction: Acquired cryptorchidism (AC) has been recognized as a subgroup of undescended testes (UDT). There is growing evidence that the compromising effect equals that of congenital UDT (cUDT). This prospective study included an extensive histological examination of biopsies taken from AC patients. Patients and methods: From August 2013 to December 2014, 21 boys (3–12 years of age) underwent testicular biopsy during orchiopexy for AC. Patient and family histories were taken. The amount of germ cells (GC) per tubule (T) and the amount of adult dark spermatogonia (Ad-S) per T were determined by resin semi-thin sections examination. The samples were also scanned for signs of malformation. Immunohistochemical stains were performed as markers for atypical germ cells. Results: Four (19%) boys were born prematurely, two (9.5%) were small for gestational age (SGA), and nine (43%) had a positive family history of UDT. The median of GC/T was 1.06 in boys <9 years, and 0.60 in boys ≥9 years. The median of Ad-S/T was 0.02 in boys <9 years and 0.01 in boys ≥9 years. There were no signs for malformation and no atypical cells. The immunohistochemical stains were negative in all specimens. Conclusions: Prematurity, SGA, and a positive family history appeared to be predictors for AC. Extensive histopathological examination of AC revealed a significant reduction of germ cell count and fertility markers, comparable with that in cUDT. The alterations were more severe in boys aged ≥9 years. It is unclear as to whether or not this was possibly caused by a longer duration of inguinal position, but this finding suggests that routine checks of testicular position throughout childhood are needed, and that there is a cause for continued efforts in educating parents and primary care physicians regarding AC. Current data support the notion of surgical correction once the diagnosis is made. Table n = 21 (n = 10 < 9 years, n = 11 > 9 years) <9 years ≥9 years Median Median Germ cells per tubule 1.06 0.60 Ad-spermatogonia per tubule 0.02 0.01